Implementasi Algoritma Bellman Ford Pada Aplikasi Pencarian Pengobatan Patah Tulang Kem Kem Terdekat di Kota Medan Berbasis Android - Surya Wijaya (JURIKOM (Jurnal Riset Komputer), 2019)
Searching for the shortest distance is a problem for people who are experiencing fractures or dislocations, because in an emergency like this there will be a big panic that often victims will experience fatal things due to delays in handling, so often the victim's family looks for the shortest path to achieving the first treatment, such as the treatment of kem fractures is one of the first examples of treatment in the treatment of fractures, the efficiency of time and cost is needed in an emergency like this, so as to minimize the fatal things that will happen to victims of fractures. One of the most effective ways in an emergency like this is to search for the fastest alternative route to get to the treatment of Kem fractures. The shortest distance search application made, based on the Bellman Ford method. The bellman ford method is an algorithm that calculates the shortest path from a single point source to find another node. The results of this study are to be able to find the closest point of treatment for Kem fracture to minimize fatalities that occur to the victim, so that the victim can be treated immediately and get treatment.